Diseño de un modelo de producción y comercialización e innovación para la confección de pantalones para mujer de la industria Miltons ubicada en Conocoto-Valle de los Chillos con aplicación a las pymes - Suntaxi Cocanguilla, Ismael Bladimir (2015)
In the development of this project is to establish and determine the design of a model of production and commercialization and innovation for making formal pants womens miltons industry located in Conocoto-valley chillos. Therefore it is necessary to conduct a market survey in order to determine the demand and supply of the product, to thereby possible to identify the buyers or consumers forthcoming final, also in shops or small businesses that would purchase formal trousers women that could be marketed. Subsequently, two types of studies where its importance lies in the study of the distribution of the operational area, and materials that could be acquired to implement the product is made. Only when determined the aforementioned studies, we proceed with the projection of revenues and costs of the new product, applying the evaluation indicators could determine the feasibility of implementing this type of garment.